Evaluation of the Effect of Hyaluronic Acid Gel on Pain, Trismus, and Edema Following Mandibular Third Molars Surgery (Journal of Hama University, 2022)
Hyaluronic Acid Gel was used to decrease Pain, Trismus, and Edema Following Mandibular Third Molars Surgery. This clinical study was carried at oral and maxillofacial surgery department at Hama university. This study included random sample of 40 cases of impacted lower third molars on 20 patients. The ages of patients were between 18-30 years. The aim of this study was was to evaluate the effect of Hyaluronic acid 0.2% on pain, edema, and trismus after impacted lower third molars surgery. The sample was divided into two groups:First group (study group): 20 impacted lower third molars was surgically extracted. Hyaluronic acid 0.2 % was applied in alveolar cavity.Second group (controlled group): 20 impacted lower third molars was surgically extracted. It wasn’t applied anything in alveolar cavity.The study showed that Hyaluronic acid 0.2% have a positive effect on controlling pain, edema, and trismus after surgical extraction at first, second, third, seventh, tenth days